2007
DOI: 10.1038/nature05455
|View full text |Cite
|
Sign up to set email alerts
|

Coupling substrate and ion binding to extracellular gate of a sodium-dependent aspartate transporter

Abstract: Secondary transporters are integral membrane proteins that catalyse the movement of substrate molecules across the lipid bilayer by coupling substrate transport to one or more ion gradients, thereby providing a mechanism for the concentrative uptake of substrates. Here we describe crystallographic and thermodynamic studies of Glt(Ph), a sodium (Na+)-coupled aspartate transporter, defining sites for aspartate, two sodium ions and d,l-threo-beta-benzyloxyaspartate, an inhibitor. We further show that helical hair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

89
1,082
8
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(1,181 citation statements)
references
References 42 publications
89
1,082
8
2
Order By: Relevance
“…Structural information is available for the glutamate transporter homolog Glt Ph from the archaeon Pyrococcus horikoshii, which is selective for aspartate rather than glutamate and which couples the uptake of substrate to the symport of three sodium ions [3][4][5][6][7][8] . The protein is a homotrimer, with each protomer consisting of two domains.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Structural information is available for the glutamate transporter homolog Glt Ph from the archaeon Pyrococcus horikoshii, which is selective for aspartate rather than glutamate and which couples the uptake of substrate to the symport of three sodium ions [3][4][5][6][7][8] . The protein is a homotrimer, with each protomer consisting of two domains.…”
mentioning
confidence: 99%
“…Different crystal structures of substrate-bound Glt Ph have revealed that the trimerization domains form a stable scaffold 6,9 . The transport domains have been captured in three states: outward facing, intermediate and inward facing [5][6][7] . The structures suggest that the transport domains behave as rigid bodies and move across the membrane like an elevator to shuttle the substrate and coupled ions from one side to the other.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is well exemplified by a recent XRC analysis of a functional double mutant of Glt Ph , a glutamate transporter from Pyrococcus horikoshii (Verdon and Boudker, 2012). While previous structure determinations captured Glt Ph (Yernool et al, 2004;Boudker et al 2007) and its analogue (Reyes et al, 2009) as symmetric trimers with all their protomers facing either outward or inward, the structure of the Glt Ph -V198CA380C Hg double mutant is an asymmetric trimer with two protomers in IFS and one in an intermediate outward-facing state (iOFS) (Fig. 4A).…”
Section: E Primary and Secondary Transportersmentioning
confidence: 82%
“…Despite the above-described data indicating that Tl ϩ can interact functionally with the transporter, this cation could not support aspartate transport (2). Therefore, the assumption that Tl ϩ faithfully mimics the action of sodium (2) must be treated with caution.…”
mentioning
confidence: 97%